2011
DOI: 10.1016/j.bpj.2011.05.070
|View full text |Cite
|
Sign up to set email alerts
|

Steps and Bumps: Precision Extraction of Discrete States of Molecular Machines

Abstract: We report statistical time-series analysis tools providing improvements in the rapid, precision extraction of discrete state dynamics from time traces of experimental observations of molecular machines. By building physical knowledge and statistical innovations into analysis tools, we provide techniques for estimating discrete state transitions buried in highly correlated molecular noise. We demonstrate the effectiveness of our approach on simulated and real examples of steplike rotation of the bacterial flage… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
50
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 28 publications
(50 citation statements)
references
References 27 publications
(35 reference statements)
0
50
0
Order By: Relevance
“…Two remarkably different behaviors can nevertheless be identified in the Past1000s: whereas the SPG weakens progressively at an almost constant rate throughout the entire last millennium in R1 and R2 (with trends of the order of −0.10 Sv/century), the SPG in R3 shows a rapid shift from a strong to a weak state around 1600. An algorithm for discrete level identification (Little et al 2011) allows an objective characterization of the shift: it occurs in about two decades, accounts for a weakening of 0.72 Sv, and separates two stationary states, each covering at least 250 years (Fig. 1a, horizontal solid lines for Past1000-R3, and Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Two remarkably different behaviors can nevertheless be identified in the Past1000s: whereas the SPG weakens progressively at an almost constant rate throughout the entire last millennium in R1 and R2 (with trends of the order of −0.10 Sv/century), the SPG in R3 shows a rapid shift from a strong to a weak state around 1600. An algorithm for discrete level identification (Little et al 2011) allows an objective characterization of the shift: it occurs in about two decades, accounts for a weakening of 0.72 Sv, and separates two stationary states, each covering at least 250 years (Fig. 1a, horizontal solid lines for Past1000-R3, and Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Horizontal dash-dotted and dashed lines respectively account for the 25th-75th and 5th-95th percentiles of the SPG strength in PiControl. Horizontal solid lines are the discrete levels extracted following the algorithm described in Little et al (2011). b Annual globally averaged values of the reconstructed TSI (black line, in W/m 2 ) (Vieira et al 2011) and the simulated volcanic forcing, shown as net adiative flux anomalies, long plus short waves (LW + SW, in W/m 2 ), at the top of the atmosphere with respect to the climatological mean.…”
Section: North Atlantic Climate Regimes Before and After The Shiftmentioning
confidence: 99%
“…Due to the stochastic nature of enzymatic stepping the number of steps is often not known a priori. Therefore, different step finding algorithms have been developed [17][18][19][20].One class of algorithms determine steps from single molecule data based on statistical hypothesis testing in a moving window. A prominent example is the so called t-test, which is based on the Student's t-test [18].…”
mentioning
confidence: 99%
“…Thus, if steps are hidden in noise such algorithms behave as efficient filter-functions, and accurate step-detection requires an additional second stage on the filtered, i.e. denoised data [20].Here, we present a novel two stage approach, termed Energy Based Stepfinding (EBS), where both stages are based on the minimisation of energy functions. In a first stage, we denoise the signal with a highly efficient and fast optimization algorithm.…”
mentioning
confidence: 99%
See 1 more Smart Citation